(untitled) (Research, Society and Development, 2021)
This study aimed at investigating the effect of fermented dairy beverage with clove essential oil (CEO) on the levels of reactive oxygen species (ROS) through endogenous enzymes superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx). For this, bioinformatic analysis was performed using the Genecards and String platforms. Headspace was used to analyze and confirm the compounds at low concentrations. Antioxidant activity was analyzed using the DPPH free radical sequestration method. For analysis of antioxidant activity, twenty-four male Swiss mice were divided into three groups and submitted histopathological analysis, analysis of CAT, SOD,GPx transcripts, and CAT and SOD enzyme activity in visceral adipose tissue were evaluated.The leader genes found were PIK3CD, PIK3CB, AKT1, and PIK3CA, as they had the highest WNL values. The beverage containing CEO showed higher antioxidant activity, with free radical scavenging capacity above 80%. In the in vivo analyses, it was possible to verify a reduction in the average adipocyte area size (μm2) between the groups that received fermented dairy beverage. Although functional studies have shown that the antioxidant enzymes, CAT and SOD, showed similar concentrations in visceral adipose tissue of the three groups, the expression levels of GPx1, CAT, and SOD were higher in group 2. Surprisingly, the group 3, that received the fermented dairy beverage with CEO had the lowest SOD concentration (p <0.05). Therefore, the antioxidant mechanism of the CEO can be mediated by the activation of the cell survival pathway PI3K/Akt and modulation of SOD1 and CAT enzymes by means of ROS reduction.